2015
DOI: 10.1186/s12906-015-0735-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of therapeutic local anesthesia (neural therapy) in 280 referred refractory chronic pain patients

Abstract: BackgroundCan the application of local anesthetics (Neural Therapy, NT) alone durably improve pain symptoms in referred patients with chronic and refractory pain?If the application of local anesthetics does lead to an improvement that far exceeds the duration of action of local anesthetics, we will postulate that a vicious circle of pain in the reflex arcs has been disrupted (hypothesis).MethodsCase series design. We exclusively used procaine or lidocaine. The inclusion criteria were severe pain and chronic du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0
16

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 32 publications
5
74
0
16
Order By: Relevance
“…22 NT is not only a local injection, but also includes segmental and supra-segmental injections and the effect of NT in other painful musculoskeletal disorders have been shown in previous studies. 11,12 According to the authors, the effects of NT in patients with LE were shown for the first time in this study, and according to our results, NT is an effective treatment modality for LE.…”
Section: <0001supporting
confidence: 73%
See 2 more Smart Citations
“…22 NT is not only a local injection, but also includes segmental and supra-segmental injections and the effect of NT in other painful musculoskeletal disorders have been shown in previous studies. 11,12 According to the authors, the effects of NT in patients with LE were shown for the first time in this study, and according to our results, NT is an effective treatment modality for LE.…”
Section: <0001supporting
confidence: 73%
“…The regulatory mechanisms of the nervous system are used mainly on segmental reflector processes and the interference field described as the zone that initiates and/or maintains pain and inflammation, regardless of the related segment. [11][12][13] The effect of NT was previously reported in various painful musculoskeletal disorders. 9,10 The authors claimed that NT is more effective than traditional treatment methods (including rest, bracing, non-steroidal anti-inflammatory drugs) in these patients.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Estos resultados coinciden con varios estudios experimentales donde se logró una disminución significativa del dolor durante las primeras semanas de tratamiento 19,20,21 .…”
Section: Discussionunclassified
“…Nöralterapi lokal anestezik maddelerin vücudun belirli noktalarına enjekte edilmesi ile nörovejetatif sinir sistemi üzerinde etki elde edilmesinin amaçlandığı bir tedavi yöntemidir (1,2). Nörovejetatif sistem vücudumuzun kapiller yapısına kadar ulaşan ve her yeri kuşatan bir network ağı gibi çalışmaktadır.…”
Section: Introductionunclassified